MAJOR PALEOGEOGRAPHIC, TECTONIC AND GEODYNAMIC CHANGES FROM THE LAST STAGE OF THE HELLENIDES TO THE ACTUAL HELLENIC ARC AND TRENCH SYSTEM - Papanikolaou, D. (Bulletin of the Geological Society of Greece, 2010)
Present day location and geometry of the Hellenic arc and trench system is only a small portion of the previously developed Hellenic arc that created the Hellenides orogenic system. The timing of differentiation is constrained in Late Miocene, when the arc was divided in a northern and a southern segment. This is based on: a) the dating of the last compressive structures observed all along the Hellenides during Oligocene to Middle-Late Miocene, b) on the time of initiation of the Kephalonia transform fault, c) on the time of opening of the North Aegean Basin and d) on the time of opening of new arc parallel basins in the south and new transverse basins in the central shear zone, separating the rapidly moving southwestwards Hellenic subduction system from the slowly converging system of the Northern Hellenides. The driving mechanism of the arc differentiation is the heterogeneity produced by the different subducting slabs in the north (continental) and in the south (oceanic) and the resulted shear zone because of the retreating plate boundary producing a roll back mechanism in the present arc and trench system. The paleogeographic reconstructions of the Hellenic arc and surrounding areas show the shortening of the East Mediterranean oceanic area, following the slow convergence rate of the European and African plates plus the localised shortening following the rapid Hellenic subduction rate. The result is that the frontal parts of the accretionary prism developed in front of the Hellenic arc have reached the African continent in Cyrenaica whereas on the two sides the basinal parts of the Ionian and Levantine basins are still preserved before their final subduction and closure. The extension produced in the upper plate has resulted in the subsidence of the Aegean Sea and the creation of several neotectonic basins in southern continental Greece in contrast to the absence of new basins in the northern segment since Late Miocene.